FRI0540 Evaluation of bone quality using the new trabecular bone score (TBS) tool in rheumatoid arthritis patients. (15th June 2017) - Casabella, A; Sulli, A; Seriolo, C; Botticella, G; Molfetta, L; Cutolo, M; Paolino, S; Ruaro, B
Abstract : Background: Patients affected by Rheumatoid Arthritis (RA) show an increased risk of low bone mass, as a result of multi-systemic disorders including toxic drug, low vitamin D levels and physical inactivity. Trabecular Bone Score (TBS), is an index extracted from the dual-energy X-ray absorptiometry (DXA) images, that provides an indirect measurement (Score) of bone axial microarchitecture and allows to get information about bone quality (1, 2). Objectives: The aim of this investigation was to evaluate bone quality in RA patients (high risk population) receiving vitamin D supplementation from at least 3 month, using the TBS. Methods: 108 female patients (mean age 61±8 years) affected by RA and 60 age- matched controls (CNT) (mean age 64±11 years) were enrolled. Bone Mineral Density (BMD, g/cm 2 ) of the lumbar spine (L1-L4) was analyzed using a DXA scan (GE, Lunar Prodigy). Lumbar spine TBS (TBS iNsight Medimaps) was derived for each spine DXA examination. All patients were evaluated for serum 25 hydroxyvitamin D (25(OH)D) concentrations. Results: 78 RA patients (80%) presented a bone loss that was significantly lower when compared with control group (p<0.001). Likewise, lumbar spine TBS score was found significantly lower in RA patients compared with CNT (p<0.001). Finally, RA patients showed lower 25(OH)D concentrations (18.4±1.3 ng/ml) than CNT (26.2±0.9 ng/ml; p<0.04). Conclusions: This study shows in RA patients a reduction of TBS values that seem placed side by side with reduced BMD values and 25(OH)D serum concentrations. Therefore, TBS could become a new and safe diagnostic tool for the quantification of the bone quality and related osteoporosis, in chronic systemic inflammatory rheumatic diseases, such as RA. References: Sinigaglia L, et al. Rheum Dis Clin North Am. 2006;32:631–58. Avouac J, et al. Arthritis Care Res 2012;64:1871–8. Disclosure of Interest: None declared